2020
DOI: 10.3389/fphar.2020.00193
|View full text |Cite
|
Sign up to set email alerts
|

The Anticancer Properties of Tanshinones and the Pharmacological Effects of Their Active Ingredients

Abstract: Cancer is a common malignant disease worldwide with an increasing mortality in recent years. Salvia miltiorrhiza, a well-known traditional Chinese medicine, has been used for the treatment of cardiovascular and cerebrovascular diseases for thousands of years. The liposoluble tanshinones in S. miltiorrhiza are important bioactive components and mainly include tanshinone IIA, dihydrodanshinone, tanshinone I, and cryptotanshinone. Previous studies showed that these four tanshinones exhibited distinct inhibitory e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
90
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(91 citation statements)
references
References 165 publications
(105 reference statements)
1
90
0
Order By: Relevance
“…The present study mainly investigated the effects of Tanshinone I (a diterpenoid quinones compound) and salvianolate (a water-soluble compound) on lung adenocarcinoma. Tanshinone I is a notable component of the fat-soluble compounds that can be isolated from Salvia miltiorrhiza (28). In the present study, hub genes and key pathways involved in lung adenocarcinoma following administration of different dosages of Tanshinone I were identified.…”
Section: Discussionmentioning
confidence: 79%
“…The present study mainly investigated the effects of Tanshinone I (a diterpenoid quinones compound) and salvianolate (a water-soluble compound) on lung adenocarcinoma. Tanshinone I is a notable component of the fat-soluble compounds that can be isolated from Salvia miltiorrhiza (28). In the present study, hub genes and key pathways involved in lung adenocarcinoma following administration of different dosages of Tanshinone I were identified.…”
Section: Discussionmentioning
confidence: 79%
“…Natural products are a good source of antitumor compounds. In recent years, auraptene have drawn scientists’ attention because of its broad-spectrum and effective antitumor activities ( Fu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Danshen (Salvia miltiorrhiza), an important traditional Chinese herb, has been used extensively as a healthy food and in clinical usage for more than 1000 years [11][12][13]. Modern advanced technological analysis has clarified that the major constituents of danshen are hydrophilic phenolic acids and lipophilic compounds [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Danshen (Salvia miltiorrhiza), an important traditional Chinese herb, has been used extensively as a healthy food and in clinical usage for more than 1000 years [11][12][13]. Modern advanced technological analysis has clarified that the major constituents of danshen are hydrophilic phenolic acids and lipophilic compounds [11][12][13]. Studies have shown that both these constituents contribute to most of the bioactivities and therapeutic capabilities of danshen, including antioxidation [13], anti-inflammation [14], and mitigation of cardiovascular diseases [15].…”
Section: Introductionmentioning
confidence: 99%